Future Teacher Training for Work in the Inclusive Education Framework. - Mykyteichuk, Khrystyna; Perepeliuk, Inna; Perkhun, Lesia; Bondarenko, Yuliia; Yakovleva, Svitlana; Sydoruk, Iryna (Revista Romaneasca Pentru Educatie Multidimensionala, 2022)
The relevance of the chosen topic is determined by the need for improvement of the inclusive education system in the current conditions as well as by the necessity to properly train and prepare future teachers for professional activity in the inclusive learning environment. In the given article, we have analyzed the developments on the topic, identified models of integration of children with special educational needs in the educational process in inclusive education. We also articulated the concept and essence of the professional readiness of future teachers. The ways to form the readiness of teachers for professional activity in the conditions of inclusive education are presented. The article analyzes the understanding of the concept of inclusive education and provides a brief overview of the studies by prominent researchers on this issue, taking into account their proposed educational values. Based on the analysis, the authors conclud that it is necessary to critically review traditional approaches to the understanding of inclusive education, and to the formation of readiness of future teachers for professional activities in inclusive education to eventually benefit modern education. The authors of the article note that in the context of professional training for teachers' activity, four main components will be effective, which will promote the integration of children with special educational needs into the educational process.
Keywords: inclusive environment, methodical readiness for pedagogical activity, professional training, change of personal indicators, special educational needs